Estimation of export specialization: Lithuanian case - Dalia Bernatonyte (Institute of Economic Research (IER), 2015)
This paper investigates the nature and pattern of export specialization in Lithuania. The aim of this paper is to estimate the nature and pattern of Lithuanian export specialization under existing conditions. Seeking to define the nature and pattern of export specialization, the basic methods of export specialization measurement and the nature and pattern of export specialization in trade between Lithuania and the EU are determined. For measurement the pattern of export specialization in Lithuania two approaches are adopted. The index of export specialization is used to determine the pattern of comparative advantage. Secondly, trade dissimilarity index is used to predict structural changes in Lithuanian exports. Using these methods of measurement and standard international trade classification (SITC) was determined the nature and pattern of Lithuanian export specialization. It was found that the biggest flows from Lithuania to the EU are in such groups: food, drink and tobacco; raw materials; mineral fuels, lubricants and related materials. These calculation results show the main directions of nature and pattern of export specialization. This research could be useful for preparing and forecasting the possibilities of Lithuanian export development.
Keywords: F1; F11; F14; 330; trade; export; export specialization; revealed comparative advantage index; trade dissimilarity index